The Silent Erosion: Investigating Body Shaming's Influence on Student Self-Esteem and Its Counseling Implications at SMA PGRI Depok - Nabilah Sakhaa Faisyah; Yuda Syahputra; Mulyadi Mulyadi; Candra Prasiska Rahmat (Asosiasi Asesmen Pendidikan (AAP), 2025)
This study aimed to examine the significant contribution of body shaming to self-esteem among students at SMA PGRI Depok. This was a quantitative, correlational study that employed a simple linear regression analysis technique. A sample of 138 students from the total population in classes ten and eleven was selected using a simple random sampling method. Research instruments, in the form of questionnaires, underwent validity and reliability testing using SPSS Statistics version 20. The findings revealed that the coefficient of determination (R²) for body shaming was 0.273. This indicated that body shaming contributed 27.3% to self-esteem, while 72.7% of the remaining variance was influenced by other factors. It was concluded that a higher experience of body shaming among students led to lower levels of self-esteem at SMA PGRI Depok.